Pengaruh Sistem Pengendalian Internal Dan Penerapan Budaya Tri Hita Karana Terhadap Pencegahan Kecurangan (Fraud) Akuntansi Pada Lembaga Perkreditan Desa (Lpd) Se- Kecamatan Abiansemal - Ni Made Ayu Indrawati; Ni Putu Ayu Kusumawati; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2023)
The research was conducted to reveal the relationship between the implementation of the Tri Hita Karana internal control system and culture towards anti-fraud actions in Village Credit Institutions (LPD) throughout the Abiansemal District. All the subjects of this study were the Chairpersons and Supervisory Boards of 32 Village Credit Institutions (LPD) in Abiansemar District, Badung Regency. The sample size for this study was 128 people. This study found that the internal control system can be a cause of preventable accounting fraud. The application of the Tri Hita Karana culture can be one way to prevent accounting fraud. Seeing this study, in the future Village Credit Institutions (LPD) throughout Abiansemal Regency will be encouraged to improve their internal control systems by ensuring that all existing LPD regulations are complied with by their employees. It is hoped that it can be improved. Violation of these regulations is subject to severe sanctions designed to build work discipline that can reduce the possibility of fraud